Mengukur stabilitas likuiditas bank syariah: kasus btn syariah 2020–2024 - Saputri, Wilyana Erfian (Maliki Interdisciplinary Journal, 2025)
This study analyzes Bank BTN Syariah’s liquidity over the past five years (2020–2024) using the cash ratio as a conservative indicator. The cash ratio was chosen because it only considers cash and cash equivalents rather than current liabilities, thus reflecting the bank’s ability to meet short-term obligations immediately. The results show a fluctuating trend, with the most significant decline in 2021 (4.79%) and moderate declines in 2023–2024 (6.87% and 8.63%), although within the safe limits of industry practice. This decline was influenced by growth in current liabilities, increased customer deposits, macroeconomic dynamics, and changes in fund placement strategies. The findings emphasize the importance of proactive liquidity management, including strengthening cash reserves, optimizing cash flow, and diversifying Sharia-compliant liquid instruments. This study also highlights the relevance of cash ratio analysis as a reference for management and regulators in maintaining liquidity stability and compliance with the prudential principles of Sharia banking. This research is expected to serve as a reference for the development of Sharia bank liquidity literature in Indonesia and as a guide for managerial strategies in the Sharia banking sector.